PENGARUH KEPERCAYAAN, PERSEPSI HARGA, DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN ONLINE SHOP DITA SHOP SEMARANG - Yudita Zafariana Ariani, 14.05.51.0166; Soliha, Euis (Students' Journal of Economic and Management, 2018)
A study of purchasing decisions is very important to be done by business people who market their products online. Online marketing is not easy, marketers must be smart in perceiving prices and promoting their sales through social media, namely through Instagram. The purpose of this promotion is so that consumers can be interested and decide to buy products at Dita Shop Semarang, besides that there is a purpose in this process that is to prove the influence of trust, price perception and sales promotion on online purchasing decisions. The population in this study are all consumers who have made purchases at Dita Shop Semarang. The sample used was 100 respondents, using non-probability sampling technique with the sampling method used was purposive sampling, namely sampling with criteria, namely respondents were adults, domiciled in the city of Semarang, people who had made purchases, who used ATMs . Research data analysis method uses linear regression. The results of this test show: (1) Prices affect the purchase decision. (2) Price Perception influences purchasing decisions. (3) Sales Promotion influences purchasing decisions. Keyword: trust, price perception, sales promotion and decisionpurchase.